Pregnancy Outcomes in Women of Advanced Age - Mehrnaz Valadan; Fatemeh Tanha; Azam Sepahi (Tehran University of Medical Sciences, 2011)
Objective: The aim of this study was to investigate prenatal and obstetrical outcome in mothers aged 40 years or older. Materials and methods: A prospective comparative study was conducted for the women aged 40 years and over who delivered at 20 week's gestation or beyond from January 2004 to December 2005 at four Hospitals of Tehran University of Medical Sciences. For comparison, a control group of patients who were 20-29 years of age was considered. Results: There were statistically significant increases in the rates of gestational diabetes, preeclampsia, caesarean section, breech presentation and stillbirth in women 40 years of age or older. Conclusion: There is a need to offer older women special counseling both before and after conception so that they become informed of the increased risks involved.